Electrochemical DNA biosensor for the detection of trichoderma harzianum. - Yusof, Nor Azah; Siddiquee, Md. Shafiquzzaman; Salleh, Abu Bakar; Abu Bakar, Fatimah (2010)

(untitled)
This invention relates to a modified electrochemical dna sensor electrode, wherein the electrode is coated with a membrane film composite comprising nanoparticles, a ionic liquid (il) and a natural polymer, specifically the membrane film composite is [emim][otf]/zno/chit. The electrochemical dna biosensor of the invention can be used for the detection of pathogens, in particular trichoderma harzianum. The inventive electrochemical dna biosensors do not only work with synthetic target dna but are also able to detect target dna in crude dna isolated from biological samples without prior amplification by polymerase chain reaction (PCR). Further disclosed are methods for the manufacturing of the inventive modified electrochemical dna sensor electrode and methods and kits for detecting the presence of pathogens in a biological sample.